(untitled) (Journal of Bangladesh Academy of Sciences, 2026)
In this study, anatase TiO2 nanoparticles (NPs) were synthesized via a hydrothermal route from titanium isopropoxide. TiO2/cellulose nanocomposites were prepared at different weight percentages (20%, 40%, and 60%) and denoted as CT20, CT40, and CT60, respectively, to enhance the photocatalytic degradation of an organic dye. The prepared composites were characterized by FTIR, XRD, FE-SEM, and UV-DRS, confirming the formation of a composite with nano-range particles and a high surface-tovolume ratio. The band gap of the prepared TiO2 NPs was found to be 3.28 eV. UV radiation was used to investigate the photocatalytic performance of the prepared materials to degrade methylene blue (MB). UV-visible absorption spectroscopy was used to monitor the decrease in MB concentration during photocatalytic experiments. Within 90 min, the removal efficiencies were 83%, 89%, 90%, and 99% for CT20, CT40, CT60, and TiO2, respectively. The dye removal per mg of TiO2 in the composite were found to be 8.3%, 4.5%, 3%, and 2%, for CT20, CT40, CT60, and TiO2, respectively. To investigate the optimum conditions for the photocatalytic degradation reaction, the effects of pH, catalyst dose, and initial dye concentration were studied. The degradation reaction of MB was followed by pseudo-first-order kinetics, with rate constants of 0.010, 0.013, 0.016, and 0.026 min-1 for CT20, CT40, CT60, and TiO2, respectively. Reusability data indicate that composite materials can be recycled across multiple life cycles without compromising cost-effectiveness. J. Bangladesh Acad. Sci. 50(2); 181–195: June 2026